MODELS AND MECHANISMS MANAGEMENT OF PROGRAM PROJECTS OF SOCIO-ECONOMIC DEVELOPMENT THE TERRITORIES - Zachko, I.; Ivanusa, A.; Zachko, O. (Scientific Journal of Astana IT University, 2020)
The scientific article considers an important scientific and applied problem of developing models and mechanisms for projects and programs management for the socioeconomic development of territories by means of financial regulation instruments. The priority of reorienting the paradigm of project management using mechanisms of financial regulation and project management is justified. The genesis of the problem of projects and programs management for the development of territorial socio-economic systems was researched on the example of leading scientific schools. An informational and literary analysis of modern trends in the implementation of large-scale programs and projects for the socio-economic development of territories was carried out on the example of Ukraine, Kazakhstan and Japan. Based on the informational and literary analysis of modern trends in the implementation of programs and projects for the socio-economic development of territories, specific categories of development projects were formulated taking into account the cross functional culture of the multi-project environment. A life cycle model has been developed for the development projects of the regional socio-economic territorial system. A definition of a regional socio-economic territorial system is given using project management definitions, in particular the concept of a project environment. The synergistic effect of the socio-economic development projects and programs is achieved precisely by integrating the best project management practices using the P2M methodology, financial regulation tools using subsidies and subventions for targeted program projects as sources of financing projects and public-private partnership mechanisms. The scientific results obtained in the article complement the existing methodology for managing programs and portfolios of regional development projects and change the vision of the value characteristics of the project by reloading the existing management paradigms using financial regulation mechanisms.